FAMILY FOOD SECURITY AND THE INCIDENT OF STUNTING TODDLERS IN EAST BARITO REGENCY CENTRAL KALIMANTAN PROVINCE - Suhaimi, Ahmad; Riniwati; Heldawati (Transpublika Publisher, 2023)
This study aims to assess family food security and its relationship with food availability, food access, and food diversity in Dusun Tengah District, East Barito Regency, Central Kalimantan Province. The research methodology involves observation, interviews, and data recording. The findings reveal that the average daily energy intake for children under five in Dusun Tengah District is 960.76 kcal/cap/day, with a PPH score of 63.7. The majority of households fall into the category of food insecurity, with a moderate level of hunger at 81.1%. Severe hunger is observed in 7.8% of households, while food insecurity without hunger is reported in 11.1% of cases, and no households are classified as food secure. Regarding food availability, all households are in the low category, accounting for 100% of respondents. In terms of food access, 39% of respondents have a distance of less than 25 minutes to the market, while 61% have access to the market within a 25-minute distance. As for food diversity, 100% of the families of toddlers’ experience food insecurity, with none in the food-safe or food-alert category. The composite index shows that no families have a food-safe status, 28% have a food-alert status, and the majority, accounting for 72%, experience food insecurity. The correlation coefficients with stunting are 0.233 for availability, 0.113 for access, and 0.081 for diversity, indicating a weak relationship between availability, access, and diversity with stunting.